Point-of-sale loyalty analysis considering store environment (online and offline) and recency of purchase - Hermenegildo Chávez, Maria Victoria (2023)
Purpose – First, to test our comparative model between online and offline purchase behavior; and, secondly, to investigate whether recency moderates the model's relationships in different periods. Theoretical framework – This study is framed by Garbarino and Johnson's (1999) theory of the roles of satisfaction, trust and commitment. Design/methodology/approach – The sample consists of 768 purchases of products/services from Peruvian consumers. To test the hypotheses we apply the structural equation modelling based on covariance (SEM). Findings – The relationship between privacy/security of purchase and quality is more intense in an offline purchase than online, while the opposite is true for the relationship between quality and trust. Also, purchase recency moderates all relationships in our loyalty model. Research Practical & Social implications – We focus this study on a Latin American country where recency of purchase takes centre stage in customer loyalty relationships. Originality/value – We provide a relevant perspective on point-of-sale loyalty in both offline and online environments, looking at the moderating role of recency of purchase (a variable that has been little researched), in the context of a developing country such as Peru.